(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study on declarative constructions in Igbo and Mandarin Chinese is necessitated by the ever increasing population of Igbo first language (L1) speakers learning Mandarin Chinese (MC) as a second language (L2). Igbo as a member of the new Benue-Congo group of the Niger-Congo language family is quite distinct from MC which is the standard variety of Chinese, a member of the Sino-Tibetan language. From the origin of both languages, it is right to assume that there could be differences in their systems and these differences could translate to impending challenges for the learners. With the application of descriptive analysis, the study examines the constituent structures of declarative sentences, pointing out their similarities and differences as obtainable in both languages. Data were elicited from grammar texts in both languages as well through native speaker intuition. Findings show that the two languages have the basic SVO word order though the constituent structures vary greatly. These differences abound in the nominal position of the determiners, the presence of numeral classifiers in Chinese NP, the position of adverbial elements, interrogative markers, as well as the negation strategies in the VP of both languages. Based on the aforementioned, this paper concludes that any Igbo L2 learner of Chinese should be mindful of the structural differences not withstanding that both languages have same basic sentence pattern so that there will be a proper understanding of the declarative operations in both languages. Such awareness in turn, should enable them to strategically adapt their learning approaches, which would enhance their performance and facilitate a more effective learning strategy for the Chinese language. This consciousness would help learners minimize learning and negative transfer.